KINERJA KEUANGAN DAN UMUR PERUSAHAAN SEBAGAI FAKTOR PENENTU TINGKAT UNDERPRICING PERUSAHAAN NON KEUANGAN YANG MELAKUKAN INITIAL PUBLIC OFFERING - Muspa Muspa (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
This study aims to analyze the Influence of Financial Performance and the age of the company against the level of underpricing in non-financial companies that conduct Initial Public Offering. The samples used in this study amounted to 44 non-financial companies experiencing underpricing. The method of analysis used in this study is multiple regression analysis with the help of SPSS version 20.0. The observation period is 3 years from 2012 to 2014. The results of this study indicate that the Return on Equity positive and not significant, Debt to Equity Ratio and age of the company have a negative and not significant. While simultaneously, the variable Return On Equity, Debt to Equity Ratio, and age of the company together have no significant effect . The influence of Return On Equity, Debt to Equity Ratio and firm age to the underpricing variable is 5.80% and the rest is influenced by other factors not studied in this research as 94,20%.